Canadian Faculty Members’ Hopes and Anxieties About the Near-Future of Higher Education - Veletsianos, George; Johnson, Nicole (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2022)
Higher education worldwide is facing several challenges spanning from economic, social, technological, demographic, environmental, to political tensions. Calls to rethink, reimagine, and reform higher education to respond to such challenges are ongoing, and need to be informed by a wide variety of stakeholders. To inform such efforts, we interviewed thirty-seven faculty members at Canadian colleges and universities to develop a greater understanding of their hopes and anxieties about the future of higher education as they considered what higher education may look like five years into the future. Results centred on four themes: (1) anxieties and hopes are shaped by supports and resources from various sources, (2) faculty members face anxiety over matters that negatively impact them but are beyond their control, (3) faculty members hope that “good” comes from the COVID-19 pandemic, and (4) faculty members hope for a well-rounded education that will enable students to succeed both within and beyond their careers. Implications for these findings suggest a need to direct research efforts and practices toward more hopeful futures for higher education, especially in the context of online and blended learning.